Eating Behavior of Imago Aulacophora similis Oliver on Cucumber (Cucumis sativus L.) with Treatment Plant Growth Promoting Rhizobacteria (PGPR) - Dwi Wulandari; Luqman Qurata Aini; Hagus Tarno (Research Journal of Life Science, 2020)
The cucumber harvests failure occurred mainly due to the destruction of crops by the leaf-eating beetle A. similis Oliver. Many ways are taken especially pesticides that are synthesized widely because it is considered the fastest and most potent to overcome pest disorders. Based on, one of the control techniques that can be used is PGPR, which is a group of bacteria that can be utilized to strengthen plants against pest attacks and plant diseases, so research needs to be done by using this technique to change the feeding behavior of the A. similis Oliver beetle on cucumber plants. The research was conducted at the Green House Department of Pest and Plant Diseases University of Brawijaya Malang in September 2018 to March 2019. It was conducted using Randomized Block Design (RBD) 5 treatment, i.e., PGPR, urea fertilizer and control (without treatment). Based on the results of the study shows that: Application of PGPR on cucumber plant can reduce damage on either leaves or flower due to the eating behavior of imago A. similis Oliver and Application of PGPR can increase the cucumber plant growth during the eating behavior of imago A. similis Oliver.